Методика моделювання та оптимізації структури посівних площ - Скляр, Олександр Григорович; Скляр, Радміла Вікторівна; Григоренко, Сергій Михайлович; Sklіar, Oleksandr; Skliar, Radmila; Hryhorenko, Serhii (Запоріжжя : 2023, 2023)
UA: В статті запропоновано методику моделювання та оптимізації структури посівних площ. Доведено, що для цього доцільно використовувати оптимізаційну економіко-математичну модель структури посівних площ. При цьому використано цільову функцію – максимум чистого доходу. Розв’язок задачі згідно запропонованої моделі передбачає розрахунок структури посівних площ продовольчих та кормових культур з обов’язковим урахуванням вимог сівозмін, які забезпечать тваринництво кормами належної якості та забезпечить прибуток від продажу товарної продукції, а також збереже природну якість ґрунтів та не порушить екосистему в цілому. В результаті рішення задачі лінійного програмування симплекс-методом MS Excel отримано оптимальну структуру посівних площ з визначеним максимальним чистим доходом. EN: The article proposes a methodology for modeling and optimizing the structure of sown areas. It is proved that it is advisable to use an optimization economic and mathematical model of the structure of sown areas. The objective function used is the maximum net income. For each agricultural enterprise, regardless of the type and form of ownership and specialization, the main task is to improve the productivity of agricultural land, to increase the volume of crop and livestock production. It is clear that this depends on many factors. A strategic reserve for increasing and rationally utilizing the commodity potential of agriculture and increasing the volume of commodity agricultural and livestock products in Ukraine is to improve the structure of crop areas. However, rational land use has always been and remains one of the key issues for both the national economy and a particular enterprise. It should be noted that the crop and livestock industries are closely interconnected. The sown areas of fodder crops depend on the specifics of crop rotations, soil type, their actual condition, and the type and volume of livestock production. The main task of calculating the structure of fodder crops is to create a reliable feed base for livestock. The solution to the problem according to the proposed model involves calculating the structure of sown areas of food and fodder crops with due regard for crop rotation requirements that will provide livestock with feed of proper quality and ensure profit from the sale of commercial products, as well as preserve the natural quality of soils and not disturb the ecosystem as a whole. As a result of solving the linear programming problem using the MS Excel simplex method, the optimal structure of sown areas with a certain maximum net income was obtained.
Methodology for modeling and optimizing the structure of sown areas
Скляр О. Г., Скляр Р. В., Григоренко С. М. Методика моделювання та оптимізації структури посівних площ. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ. 2023. Вип. 13, том 1. C. 93-105.
Keywords: моделювання; оптимізація; посівна площа; дохід; корма; скотарство; цільова функція; система змінних; modeling; optimization; sown area; income; feed; livestock; objective function; system of variables